Spinal cord anaplastic astrocytoma with BRAF V600E mutation: A case report and review of literature. Issue 3 (27th January 2020) - Takamiya, Soichiro; Hatanaka, Kanako C.; Ishi, Yukitomo; Seki, Toshitaka; Yamaguchi, Shigeru
Abstract : A 17‐year‐old female complained of lower extremity pain that progressed to low back pain accompanied by paraparesis. Magnetic resonance imaging revealed a mass in the conus medullaris of the spinal cord at the thoracic spine 11–12 level. The patient underwent resection of the mass. The pathological diagnosis was anaplastic astrocytoma based on the densely proliferating astrocytic tumor cells without necrosis or microvascular proliferation. The patient received chemoradiotherapy with oral temozolomide and a total of 54 Gy of local irradiation, followed by 24 courses of temozolomide as maintenance chemotherapy. The patient survived for 8 years without tumor recurrence following the initial treatment. Genetic analysis of the tumor revealed a BRAF V600E mutation that has not yet been reported in spinal cord high‐grade gliomas (HGGs). In recent years, the molecular therapy targeting the BRAF V600E mutation has been applied in clinical practice for several cancer types. Although the frequency in spinal cord HGGs is uncertain, it is necessary to investigate BRAF V600E mutation as a potential therapeutic target in the future.